2011
DOI: 10.1073/pnas.1018301108
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of antibiotic targets has widely varying effects on growth

Abstract: It is often assumed that antibiotics act on the most vulnerable cellular targets, particularly those that require limited inhibition to block growth. To evaluate this assumption, we developed a genetic method that can inducibly deplete targeted proteins and that mimics their chemical inactivation. We applied this system to current antibiotic targets in mycobacteria. Although depleting some antibiotic targets significantly perturbs bacterial growth, surprisingly, we found that reducing the levels of other targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
201
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(208 citation statements)
references
References 34 publications
6
201
1
Order By: Relevance
“…However, this is often prevented by transcriptional leakiness, slow or incomplete depletion of transcriptionally regulated gene products, mutations that interfere with regulation, or a combination thereof (6,7,30). Here we demonstrated that these problems can be drastically reduced or overcome entirely with a switch that combines transcriptional repression with regulated proteolysis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, this is often prevented by transcriptional leakiness, slow or incomplete depletion of transcriptionally regulated gene products, mutations that interfere with regulation, or a combination thereof (6,7,30). Here we demonstrated that these problems can be drastically reduced or overcome entirely with a switch that combines transcriptional repression with regulated proteolysis.…”
Section: Discussionmentioning
confidence: 85%
“…For the development of antibacterials, this need was initially thought to be addressable with recombinant genetic technologies that enabled both untargeted genome-wide mutations and targeted gene deletions (2). Subsequent advances achieved conditional transcriptional silencing of genes, which allowed for the identification of targets whose functions are essential both to normal physiology of the cell and to metabolism in the context of the pathophysiology of the disease of interest (3)(4)(5)(6). Notwithstanding, such advances have failed to address that drugs act on a time scale much faster than those associated with changes in de novo transcription and that many genetic approaches only achieve narrow ranges of regulation (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this suggests the potential application of regulated expression systems to the question of target vulnerability, which can be defined as the degree of inhibition of the target's function, such as enzymatic activity, that is required to impact cellular function detrimentally. 18 The possibility of prioritising according to vulnerability could, therefore, ensure the allocation of maximum resources to the most tractable targets. A recent system for regulated protein degradation 18 provided convincing evidence that the level of inhibition required to impact cellular function is target-specific, reinforcing the idea that target vulnerability might offer a more sophisticated measure in the validation process.…”
Section: When Is a Target Validated?mentioning
confidence: 99%
“…18 The possibility of prioritising according to vulnerability could, therefore, ensure the allocation of maximum resources to the most tractable targets. A recent system for regulated protein degradation 18 provided convincing evidence that the level of inhibition required to impact cellular function is target-specific, reinforcing the idea that target vulnerability might offer a more sophisticated measure in the validation process.…”
Section: When Is a Target Validated?mentioning
confidence: 99%